1995
DOI: 10.1063/1.113475
|View full text |Cite
|
Sign up to set email alerts
|

Beryllium diffusion in GaAs/AlGaAs single quantum well separate confinement heterostructure laser active regions

Abstract: Beryllium (Be) diffusion into the active layers of single quantum well separate confinement heterostructure lasers grown by molecular beam epitaxy is investigated using photoluminescence absorption spectroscopy, secondary ion mass spectroscopy, capacitance–voltage profiling, and laser threshold current measurements. A significant amount of Be diffusion occurs under normal growth conditions. Large concentrations of Be in the quantum well are correlated to the lack of an exciton feature in the absorption spectru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Our numerical calculations showed that the existence of inhomogeneous doping can strongly modify the electronic properties of doped quantum wells, being at least as important as nonabrupt interface effects. Despite limitations on the knowledge of Si diffusion in GaAs and Al x Ga 1−x As [16], and the limited spatial resolution (∼30 nm) achieved nowadays by the experimental methods used to probe dopant profiles [4][5][6][7], we believe that future experiments on inhomogeneous doping characterization and on the electron intersubband transitions in inhomogeneous doped single nonabrupt GaAs/Al x Ga 1−x As quantum wells will validate the assumptions of our inhomogeneous doping model and confirm our main results.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…Our numerical calculations showed that the existence of inhomogeneous doping can strongly modify the electronic properties of doped quantum wells, being at least as important as nonabrupt interface effects. Despite limitations on the knowledge of Si diffusion in GaAs and Al x Ga 1−x As [16], and the limited spatial resolution (∼30 nm) achieved nowadays by the experimental methods used to probe dopant profiles [4][5][6][7], we believe that future experiments on inhomogeneous doping characterization and on the electron intersubband transitions in inhomogeneous doped single nonabrupt GaAs/Al x Ga 1−x As quantum wells will validate the assumptions of our inhomogeneous doping model and confirm our main results.…”
Section: Resultssupporting
confidence: 66%
“…Following indications of experimental results concerning inhomogeneous doping patterns [4][5][6][7], we described the inhomogeneous Si-doping concentration profile N D (z) in the growth direction z by the following expression:…”
Section: The Inhomogeneous Doping Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, better device performances should be observed with the use of heterostructures with abrupt doping profiles, a fact that made the reduction of impurity interdiffusion an important research topic in semiconductor physics. However, there are experimental evidences indicating that the actual doping profiles are not abrupt [5,6] and this is due to limitations in the control of impurity implantation during the growth process, as well as to dopant diffusion/segregation during the deposition and posterior annealing [7,8]. Additionally, there is also experimental evidence supporting the existence of graded interfaces in GaN/AlGaN quantum wells [9,10].…”
mentioning
confidence: 99%